2015
DOI: 10.1021/acs.analchem.5b02639
|View full text |Cite
|
Sign up to set email alerts
|

Reversible or Not? Distinguishing Agglomeration and Aggregation at the Nanoscale

Abstract: Nanoparticles are prone to clustering either via aggregation (irreversible) or agglomeration (reversible) processes. It is exceedingly difficult to distinguish the two via conventional techniques such as dynamic light scattering (DLS), nanoparticle tracking analysis (NTA), or electron microscopy imaging (scanning electron microscopy (SEM), transmission electron microscopy (TEM)) as such techniques only generally confirm the presence of large particle clusters. Herein we develop a joint approach to tackle the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
110
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(119 citation statements)
references
References 33 publications
4
110
0
Order By: Relevance
“…Agglomeration is a case in which the dispersed particles in solution are held together by weak interactions, ultimately resulting in phase separation, and the entire process is reversible, whereas aggregation is defined as particles joining by strong bonding interactions among the colloidal particles, and the clustering is irreversible. 38 Accordingly, we deduced that the increasing pH induced an increase in the weak interactions (for example, the Van der Waals forces and hydrogen bonding) among the Ag NCs and that although there is no direct contact between the citrate and Ag atoms after thiol etching, the citrate had a significant role in determining the reversible agglomeration and dispersion behavior of the prepared Ag NCs. We found that the fluorescence intensity and absorbance of the purified Ag NCs solutions maintained good linear relationships with the pH in the range of pH 5-7 (Supplementary Figure S9) and decreased with increasing pH; the reaction time required was greatly reduced in the purified Ag NCs solutions compared with that of the unpurified Ag NCs at the same pH (pH 7).…”
Section: Resultsmentioning
confidence: 94%
“…Agglomeration is a case in which the dispersed particles in solution are held together by weak interactions, ultimately resulting in phase separation, and the entire process is reversible, whereas aggregation is defined as particles joining by strong bonding interactions among the colloidal particles, and the clustering is irreversible. 38 Accordingly, we deduced that the increasing pH induced an increase in the weak interactions (for example, the Van der Waals forces and hydrogen bonding) among the Ag NCs and that although there is no direct contact between the citrate and Ag atoms after thiol etching, the citrate had a significant role in determining the reversible agglomeration and dispersion behavior of the prepared Ag NCs. We found that the fluorescence intensity and absorbance of the purified Ag NCs solutions maintained good linear relationships with the pH in the range of pH 5-7 (Supplementary Figure S9) and decreased with increasing pH; the reaction time required was greatly reduced in the purified Ag NCs solutions compared with that of the unpurified Ag NCs at the same pH (pH 7).…”
Section: Resultsmentioning
confidence: 94%
“…By measuring the charge consumed during each NP collision, it has been proposed that the size of the colliding NP can be inferred by Faraday's law. 1621 However, this requires that the I – t transient is measured with high accuracy and that the whole particle is oxidized while in contact with the surface in a single impact.…”
Section: Introductionmentioning
confidence: 99%
“…20) to 100 nm, 18 and it has consequently been argued that impact coulometry can be used as a method for in situ determination of the size, with nm resolution, of colloidal NPs of different materials such as Ag, 1820 Cu, 22 Mo, 23 C-60, 24 Au 25 or to address colloidal stability and aggregation phenomena. 17,21 However, none of these studies provided a thorough analysis of the recorded I – t transients nor examined, with the same experimental setup, the landing of NPs with diameters spanning the range claimed. Moreover, recent work shows that the electrochemical dissolution of single NPs is a somewhat more complex process.…”
Section: Introductionmentioning
confidence: 99%
“…This difference was attributed to the ability of the NP impact method to differentiate between irreversible aggregates and reversible agglomerates in solution. 29 Most relevant to the present study, however, is the work of Koper and coworkers, 33 who discovered evidence of aggregation in a NIE system based on electrocatalytic amplification (ECA), a detection strategy first demonstrated by Bard and coworkers. [1][2] The ECA method for sensing individual NP/electrode collisions relies on the detection of a burst of current when a NP strikes an inert UME and catalyzes the oxidation or reduction of active molecules in solution.…”
mentioning
confidence: 99%